PERAN UNITED NATIONS ENTITY FOR GENDER EQUALITY AND THE EMPOWERMENT OF WOMEN (UN WOMEN) TERHADAP PENANGANAN KASUS FEMICIDE DI GUATEMALA TAHUN 2015-2020 - Umroh (2023)
This study aims to explain how UN Women as an international organization plays a role in reducing the level of femicide in Guatemala. This study uses qualitative methods with library research data collection techniques as a secondary source. International organization theory and the concept of gender based violence were used to help answer the research questions. The results of the study show that the high rate of gender-based violence in Guatemala is caused by the machismo culture that is inherent in a patriarchal society and the long history of civil war has also influenced acts of violence in people's lives in Guatemala causing people to get used to violence and normalize violence, especially against women. Seeing this situation, UN Women as an international organization to defend women's rights is moving to play its role to deal with this problem. UN Women's role in dealing with the problem of femicide in Guatemala can be seen by playing its role as an instrument, arena and independent actor through its various programs, namely the Spotlight Initiative Program, City Safe City and Safe Public Space Programmer, Forum Regional Conference on Women in Latin America and the Caribbean, the UNiTE Campaign and the HeForShe Campaign. Even though her efforts to run were faced with various obstacles, her involvement in dealing with femicide led to a decrease in the number of femicide, even though femicide still exists in Guatemala today